Личные записи как надежда на жизнь (Блокадная книга Алеся Адамовича и Даниила Гранина) - Szewczenko, Ludmiła (Studia Rossica Posnaniensia, 2022)
In recent years there has been a rise in interest in documentary works based on personal memories of participants and witnesses of different events. A book of the blockade by Ales Adamovich and Daniil Granin is based on the recollections and diaries of Leningrad residents who survived the blockade. It carries great emotional, philosophical and moral weight, and gives an understanding to what the residents of the city believed in and hoped for. Using the materials of A book of the blockade the author of the article aims to analyze how documents and the writers’ side notes affect a reader, and pinpoint the ways of presenting the notion of hope in the authentic diaries of Leningrad residents. As a result of the analysis of the mentioned text, the author reaches a conclusion that in the diaries the feeling and the emotion of hope is continuously updated in the course of creation of personal diaries by Leningrad residents. The concept of hope reflected on in A book of the blockade has a complex content, which can be associated with the triune concept of faith-hope-love. In the discourse of the authors, the concept preserves its Christian meaning – the spiritual salvation of a person. Yet its specifics is that the religious component is initially missing, and is subsequently gained through considerable changes that happen within and without those whose testimonies are collected in the book, and within and without the authors of the text, Adamovich and Granin.